(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
In this article, the role of interesting tasks in teaching students mathematical operations in mathematics lessons is to stimulate at least a slight interest in mathematics among students. As a result, the level of students’ mathematical knowledge increases, and they begin to study all topics of mathematics more deeply